Qingrequzhuo capsule alleviated methionine and choline deficient diet-induced nonalcoholic steatohepatitis in mice through regulating gut microbiota, enhancing gut tight junction and inhibiting the activation of TLR4/NF-κB signaling pathway - Lv, Shuquan; Zhang, Zhongyong; Su, Xiuhai; Li, Wendong; Wang, Xiaoyun; Pan, Baochao; Li, Hanzhou; Zhang, Hui; Wang, Yuansong (Frontiers in Endocrinology, 2023)
Qingrequzhuo capsule (QRQZ)has been used to treat nonalcoholic steatohepatitis (NASH) in clinic. However, the mechanism of QRQZ on NASH remains unclear. Recent studies have found that the dysfunction of gut microbiota could impair the gut barrier and induce the activation of TLR4/NF-κB signaling pathway, and further contribute to the inflammatory response in NASH. Modulating the gut microbiota to reduce inflammation could prevent the progression of NASH. In this study, a mouse model of NASH was generated by methionine and choline deficient (MCD) diet and treated with QRQZ. First, we evaluated the therapeutic effects of QRQZ on liver injury and inflammation in the NASH mice. Second, the changes in the gut microbiota diversity and abundance in each group of mice were measured through 16S rRNA sequencing. Finally, the effects of QRQZ on gut mucosal permeability, endotoxemia, and liver TLR4/NF-κB signaling pathway levels were examined. Our results showed that QRQZ significantly reduced the lipid accumulation in liver and the liver injury in NASH mice. In addition, QRQZ treatment decreased the levels of inflammatory cytokines in liver. 16S rRNA sequencing showed that QRQZ affected the diversity of gut microbiota and affected the relative abundances of Dubosiella, Lachnospiraceae_NK4A136_group, and Blautiain NASH mice. Besides, QRQZ could increase the expression of tight junction proteins (ZO-1 and occludin) in gut and decrease the lipopolysaccharide (LPS) level in serum. Western blot results also showed that QRQZ treatment decreased the protein expression of TLR4, MyD88 and the phosphorylation of IκB and NF-κBp65 and qPCR results showed that QRQZ treatment down-regulated the gene expression of interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α in liver. In conclusion, our study demonstrated that QRQZ could reduce the lipid accumulation and inflammatory response in NASH model mice. The mechanisms of QRQZ on NASH were associated with modulating gut microbiota, thereby inducing the tight junction of gut barrier, reducing the endotoxemia and inhibiting the activation of TLR4/NF-κB signaling pathway in liver.